A MODEL FOR ECONOMIC GROWTH IN BOSNIA AND HERZEGOVINA - Joseph W. H. Lough (Economic Review)
In the early 1990s, when the break-up of the soviet bloc spread to the Balkans, dominant neoliberal economic wisdom recommended swift privatization of public assets,  deregulation, and dismantling of the social safety net. Building upon the research of one of neoliberalism’s leading architects, this paper examines why enacting neoliberal economic and social policies in Bosnia and Herzegovina have led to outcomes contrary to those predicted by traditional neoliberal theory. We conclude by offering five policy recommendations that should, when enacted, reduce market distortions and yield significant economic growth.